2008
DOI: 10.1529/biophysj.106.98590
|View full text |Cite
|
Sign up to set email alerts
|

Modifying L-Type Calcium Current Kinetics: Consequences for Cardiac Excitation and Arrhythmia Dynamics

Abstract: The L-type Ca current (I(Ca,L)), essential for normal cardiac function, also regulates dynamic action potential (AP) properties that promote ventricular fibrillation. Blocking I(Ca,L) can prevent ventricular fibrillation, but only at levels suppressing contractility. We speculated that, instead of blocking I(Ca,L), modifying its shape by altering kinetic features could produce equivalent anti-fibrillatory effects without depressing contractility. To test this concept experimentally, we overexpressed a mutant C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 27 publications
3
60
0
Order By: Relevance
“…In another example, Mahajan et al showed that I CaL can be targeted to increase dynamic wave stability by maintaining action potentials without depressing contractility (172). Mahajan et al showed that in rabbit ventricular myocytes, when I CaL inactivation is inhibited/delayed, and when these myocytes were also treated with verapamil (an I CaL blocker), the intracellular Ca + 2 transients were not affected; the action potential duration restitution slope was flattened; and action potential duration alternans (beat-to-beat alternation in action potential duration) were prevented (172). In fact, this approach has been proposed as the possible therapeutic way to increase the usability/safety of I CaL blockers as antiarrhythmic drugs.…”
Section: Fig 6 Effect Of Ros On Various Camentioning
confidence: 99%
“…In another example, Mahajan et al showed that I CaL can be targeted to increase dynamic wave stability by maintaining action potentials without depressing contractility (172). Mahajan et al showed that in rabbit ventricular myocytes, when I CaL inactivation is inhibited/delayed, and when these myocytes were also treated with verapamil (an I CaL blocker), the intracellular Ca + 2 transients were not affected; the action potential duration restitution slope was flattened; and action potential duration alternans (beat-to-beat alternation in action potential duration) were prevented (172). In fact, this approach has been proposed as the possible therapeutic way to increase the usability/safety of I CaL blockers as antiarrhythmic drugs.…”
Section: Fig 6 Effect Of Ros On Various Camentioning
confidence: 99%
“…This latter mutation was used previously to inactivate EF-hand Ca 2Ï© -binding sites in cardiac troponin C (10), skeletal troponin C (11), and myosin regulatory light chain (12). Mutation of position 1 has been used extensively to assess the relative functional contribution of Ca 2Ï© binding to the N-and C-domain of CaM by expression of the mutated proteins in cells (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Thus, we elected to convert Asp to Ala in the first ligand position in all CaM Ca 2Ï© -binding mutants.…”
mentioning
confidence: 99%
“…Indeed, myocytes overexpressing CaM 1234 exhibit markedly prolonged action potentials. 148,149 These studies highlighted the importance of CaM in the heart, adding credence to the widespread belief that naturally-occurring mutant CaMs would likely be so deleterious to be incompatible with life. However, it was not until a decade later, that a rare group of diseases resulting from heterozygous missense mutations within one of the 3 genes (CALM1-3) encoding identical CaM proteins was discovered.…”
Section: C In Systemsmentioning
confidence: 87%